Leadership - Marian Iszatt-White and Christopher Saunders ([New York] Gildan Media Corporation, 2020)
Written by an author team from one of Europe's leading management schools, Leadership encourages critical appraisal of the mainstream viewpoints and personal reflection on leadership experience in a way that is both clear and highly engaging.
Keywords: Leadership